Awareness of Precancerous Lesions and Conditions among Dental Students and Fresh Graduates - Ahmad Liaquat, Absar Akram, Muhammad Abbas, Bilal Hussain, Ehsan Ul Haq, S. S. Masood Tirmazi, Ali H. Cheema, Abeera Ali Mir (Pakistan Journal of Medical & Health Sciences, 2022)
The purpose of this article is to gauge the level of understanding regarding oral precancerous lesions and conditions of fresh graduates and underscore the underlying deficiencies present to amplify the early detection rate in a bid to decrease mortality associated with this disease. A precancerous lesion is a structurally altered tissue with an increased risk of conversion into cancer. Similarly, precancerous condition points toward such a multifaceted condition in which an individual has a predisposition to developing cancer. Both of these terms are linked with the statistical significance that points towards the potential of a precancerous lesion or condition to transform into a malignancy. Their timely diagnosis is the focal point that will dictate prognosis, treatment modality to be used and the morbidity associated with it. Oral cancers happen to be one of the leading causes of death worldwide and they are running rampant in Asian countries because of the increased frequency of adopting high-risk factor habits such as smoking tobacco. Dentists are a class of professional healthcare workers that are almost exclusively concerned with the head and neck region of the patient. Their advanced knowledge in regards to oral cancer can facilitate an opportune diagnosis which will substantially decrease the incidences of under-treatment and over-treatment. Diagnosing precancerous lesions is curative while a delay in interpreting the lesion timely can have far-ending consequences. Keywords: Pancreous lesions, dental students, fresh graduates